(untitled) (Fiep Bulletin - online, 2013)
Doubtlessly there are sensible changes in the urban panorama with the advent of what Brazilian authorities had stipulated to call “Zero Tolerance” in respect to alcoholic beverage consumption by drivers. Although it should be the rule the law itself, the impact is of a new thing, assuming characteristics of a measure of exception which constitutes factor of risk for the society. Media usually is responsible for denounce the abusive alcoholic beverage consumption by adolescents, fact that in the Friday nights and weekends are directly linked to another harmful phenomenon: the violence in transit and its tragic consequences. The study was conducted in the city of Rio de Janeiro with adolescents that go to bars and convenience stores in gas stations on Friday nights and weekends and who have the “combined program” as a routine, that is, stopping in a “place of meeting” (point), before going to ballads. The inquiry aimed to determine the modus operandi, the type and the amount of alcoholic beverage consumption by the subjects.